Electrospun nanosized cellulose fibers using ionic liquids at room temperature - Freire, Mara G. (2011)
Aiming at replacing the noxious solvents commonly employed, ionic-liquid-based solvents have been recently explored as novel non-volatile and non-flammable media for the electrospinning of polymers. In this work, nanosized and biodegradable cellulose fibers were obtained by electrospinning at room temperature using a pure ionic liquid or a binary mixture of two selected ionic liquids. The electrospinning of 8 wt% cellulose in 1-ethyl-3-methylimidazolium acetate medium (a low viscosity and room temperature ionic liquid capable of efficiently dissolving cellulose) showed to produce electrospun fibers with average diameters within (470 ± 110) nm. With the goal of tailoring the surface tension of the spinning dope, a surface active ionic liquid was further added in a 0.10 : 0.90 mole fraction ratio. Electrospun cellulose fibers from the binary mixture composed of 1-ethyl-3-methylimidazolium acetate and 1-decyl-3-methylimidazolium chloride ionic liquids presented average diameters within (120 ± 55) nm. Scanning electron microscopy, X-ray diffraction analysis, nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy, and thermogravimetric assays were used as core methods to evaluate the structural integrity, morphology and crystallinity of the raw, electrospun, and regenerated samples of cellulose. Moreover, the photoluminescence spectra of both raw and electrospun fibers were acquired, and compared, indicating that the cellulose emitting centers are not affected by the dissolution of cellulose in ionic liquids. Finally, the use of non-volatile solvents in electrospinning coupled to a water coagulation bath allows the recovery of the ionic fluid, and represents a step forward into the search of environmentally friendly alternatives to the conventional approaches.